A Dorsal Approach for Ulnar Shortening Osteotomy - Notermans, Bo J. W.; Maarse, Wiesje; Schuurman, Arnold H. (Journal of Wrist Surgery, 2018)
Aim This study aims to evaluate the long-term complications, results, and patient satisfaction rates of a dorsally approached ulnar shortening osteotomy for ulnar impaction syndrome.Methods A retrospective chart review of 20 patients was performed. Primary outcomes of interest were subjective, measured using the Patient-Rated Wrist Evaluation (PRWE) score, Disability of the Arm, Shoulder, and Hand (DASH) score, and the third questionnaire about patient satisfaction, composed by the authors. Secondary outcomes included hardware removal due to irritation and other complications.Results Mean postoperative functional score of PRWE was 28 (standard deviation [SD], 30) and DASH 20 (SD, 26), respectively. Fifteen patients were satisfied with the operation. Removal of hardware was noted in six patients. In one patient plate breakage occurred.Conclusion Similar postoperative functional scores and complications were seen in patients undergoing an ulnar shortening osteotomy with a dorsally placed plate for ulnar impaction syndrome, compared with other plate placement localizations. The incidence of plate removal is also comparable to previously described results. As the dorsally placed plate and freehand technique, are relatively easy, we feel that it has a place in the treatment of ulnar impaction syndrome.Level of Evidence Level IV, retrospective cohort study.
Keywords: ulnar shortening osteotomy; dorsal approach; hardware removal; ulnar impaction syndrome